The art of tonal analysis : twelve lessons in Schenkerian theory - Schachter, Carl; Straus, Joseph Nathan (Oxford University Press, 2018)
Carl Schachter is the world’s leading practitioner of Schenkerian theory and analysis as applied to the masterworks of the tonal tradition. Although his articles and books have been broadly influential, perhaps his greatest impact has been felt in the classroom, at a variety of institutions. In fall 2012, Schachter taught a special doctoral seminar at the City of New York (CUNY) Graduate Center, where he talked about the music and the musical issues that have concerned him most deeply. This book consists of edited transcripts of those lectures.